1998
DOI: 10.1177/1077727x980271004
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and Acculturation: Influences on Asian American Consumers' Purchase Decision Making for Social Clothes

Abstract: The increased ethnic diversity of the U.S. population and especially the rapid growth of Asian American markets make it critical to assess the importance of developing marketing strategies specifically targeted to these particular ethnic market segments. These circumstances naturally call for an investigation of differences and similarities among various segments within the market to examine whether undifferentiated or diferentiated target marketing is necessary to reach various Asian American subgroups. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 34 publications
1
51
0
Order By: Relevance
“…For example, variation in language, religion, spending power, or attitudes/beliefs could account for the present findings (Kang & Kim, 1998). Research showed that Asian-born consumers prefer a nonverbal, literal message which may explain the reason their evaluation and selection criteria is different from Australian-born consumers and identification of this criterion is crucial for automobile marketers.…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 81%
“…For example, variation in language, religion, spending power, or attitudes/beliefs could account for the present findings (Kang & Kim, 1998). Research showed that Asian-born consumers prefer a nonverbal, literal message which may explain the reason their evaluation and selection criteria is different from Australian-born consumers and identification of this criterion is crucial for automobile marketers.…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 81%
“…The Russian version contained additional items to measure exposure to American culture. Kang and Kim (1998) recommend measuring cultural exposure through length of stay in the country and the extent of interpersonal communications with members of the culture. Thus, in accordance with their recommendation, the Russian version included items to measure the number of years the Russian immigrants had lived in the United States and the percentage of their friends who are either American-born or Russian-born.…”
Section: Surveymentioning
confidence: 99%
“…Immigrants are challenged to navigate this consumer society and learn American consumption-related attitudes, behaviors, knowledge, and skills (Kang and Kim, 1998). Immigrants may, for example, adapt their media usage (Lee and Tse, 1994a), shopping rituals, and consumer decision-making processes (Lee and Tse, 1994b;Kang and Kim, 1998) or, given differing advertising practices between the United States and less consumer-oriented societies (Wells, 1994;James, 1995), learn new methods for processing advertisements.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 481 useable surveys were collected from three groups (Chinese: 185, Japanese: 185, Korean: 144). Kang and Kim (1998) found that Chinese respondents were more likely to rely on family/relatives than were their Japanese and Korean counterparts when they purchased social clothes. In terms of acculturation, people with high acculturation levels were more likely to rely on ethnic coworkers than those with low acculturation level.…”
Section: Consumption Behavior Among Ethnic Minority Groupsmentioning
confidence: 99%
“…This finding was also consistent with the result found in the United States, where parents were less likely to acculturate to the host culture. Kang and Kim (1998) attempted to see if there were differences in the decisionmaking patterns for purchasing social clothes (clothes worn in social settings or for social event) among three major Asian American groups (Chinese, Japanese, and Korean). In addition, they investigated how Asian Americans' acculturation levels influenced decision-making patterns for purchasing social clothes.…”
Section: Consumption Behavior Among Ethnic Minority Groupsmentioning
confidence: 99%